1997
DOI: 10.1086/118609
|View full text |Cite
|
Sign up to set email alerts
|

Dust and Recent Star Formation in the Core of NGC 5253

Abstract: Ultraviolet and optical narrow and broad band images of NGC5253 obtained with the Hubble Space Telescope Wide Field and Planetary Camera 2 are used to derive the properties of the dust distribution and the recent star formation history of this metal-poor dwarf galaxy. Corrections for the effects of dust are important in the center of NGC5253: dust reddening is markedly inhomogeneous across the galaxy's central 20 ′′ region. One of the most obscured regions coincides with the region of highest star formation ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
287
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(320 citation statements)
references
References 55 publications
28
287
5
Order By: Relevance
“…Calzetti et al (1997) found that they span a range of masses and ages, and identified six main clusters, one of which powers a giant HII region that is the most prominent object in the galaxy (Vanzi & Sauvage 2004). Cresci et al (2005) detected more than 300 clusters combining high-resolution NIR and optical imaging, with derived ages spanning a range between 2 and 50 Myr and masses of up to 10 6 M .…”
Section: Ngc 5253mentioning
confidence: 99%
See 1 more Smart Citation
“…Calzetti et al (1997) found that they span a range of masses and ages, and identified six main clusters, one of which powers a giant HII region that is the most prominent object in the galaxy (Vanzi & Sauvage 2004). Cresci et al (2005) detected more than 300 clusters combining high-resolution NIR and optical imaging, with derived ages spanning a range between 2 and 50 Myr and masses of up to 10 6 M .…”
Section: Ngc 5253mentioning
confidence: 99%
“…Moreover, star-forming regions with properties consistent with the more massive HII regions detected locally are observed up to z ∼ 5 (Swinbank et al 2009), and local dwarf galaxies have been identified as scaled down analogs of clumpy starforming galaxies at high redshift (Elmegreen et al 2009). Dwarf for He 2-10, the clusters (L1-6) from Cabanac et al (2005) and the radio knots (knot 1-5) from Kobulnicky & Johnson (1999) are marked, while for NGC 5253 the clusters from Calzetti et al (1997) and Vanzi & Sauvage (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Caldwell & Phillips 1989;Martin & Kennicutt 1995;Calzetti et al 1997Calzetti et al , 1999). We will highlight here only those observations that are relevant to our present work.…”
Section: Introductionmentioning
confidence: 99%
“…4 (≈ 5 pc). The eastern cluster coincides with the peak of the Hα emission in NGC 5253 and is the youngest optical star cluster identified by Calzetti et al (1997). The western cluster is very reddened and is coincident with the supernebula of Turner et al (2000).…”
Section: Introductionmentioning
confidence: 63%